Social Policy for Health & Social Care - Lovell, Tina.; Cordeaux, Claire (London : Hodder & Stoughton Educational, 1999)
While there are a growing number of social policy texts aimed at degree level students, there is currently very little to support students or teachers at FE level. This book has been written to meet the needs of these courses.
Includes bibliographical references (p. 175-176) and index.
Keywords: Social policy; Human services; Society